From Pasha to Cleopatra and Vashti: the oriental other in Charlotte Brontë’s Villette - Mohd Ramli, Aimillia (Maney Publishing, 2010)
Critics have argued that Jane’s engagement with the Orient in Jane Eyre (1847) is grounded in the vocabulary of her role as liberator and the discourse of female slavery and male domination as represented by the use of the harem metaphor in the text. Yet little is said about how this same metaphor exposes in Villette (1853) the ambivalence inherent in the construction of a Western character that has been invaded by the so-called menacing influences of the Orient. In the novel, the Oriental familial institution of the harem is figuratively and literally seen as a contaminant that poses a threat to a racial and gendered colonial British character. It suggests that this contamination destabilizes this character, blurring the line that divides both East and West, fantasy and reality, and argues that the Oriental institution of the harem, the artistic representations of women as illustrated by the Orientalist portrait of Cleopatra and the actress playing Vashti and, finally, M. Paul, represent the different ways in which this character is gendered and orientalized.